2018
DOI: 10.1093/jnen/nly064
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of a Case With Fatal CAR T-Cell-Associated Cerebral Edema

Abstract: Chimeric antigen receptor (CAR) T cells are a new and powerful class of cancer immunotherapeutics that have shown potential for the treatment of hematopoietic malignancies. The tremendous promise of this approach is tempered by safety concerns, including potentially fatal neurotoxicity, sometimes but not universally associated with cytokine release syndrome. We describe the postmortem examination of a brain from a 21-year-old patient with relapsed pre-B cell acute lymphoblastic leukemia (ALL) who died from ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 16 publications
3
71
0
2
Order By: Relevance
“…Others have also reported efficient CNS trafficking of CAR-T cells without an increase in neurotoxicity, 28 and pathology studies have shown limited inflammatory infiltrates in the brain after cerebral edema during CAR-T cell treatment. 9,41 CD4 + CAR-T cells were over-represented in the CSF of patients with neurotoxicity, similar to findings in adults. 9 Further study will be needed to determine what mechanisms are responsible for this bias in T cell subsets, and whether CAR-modified T cells participate in pro-or anti-inflammatory signaling in the CNS.…”
Section: Discussionsupporting
confidence: 76%
“…Others have also reported efficient CNS trafficking of CAR-T cells without an increase in neurotoxicity, 28 and pathology studies have shown limited inflammatory infiltrates in the brain after cerebral edema during CAR-T cell treatment. 9,41 CD4 + CAR-T cells were over-represented in the CSF of patients with neurotoxicity, similar to findings in adults. 9 Further study will be needed to determine what mechanisms are responsible for this bias in T cell subsets, and whether CAR-modified T cells participate in pro-or anti-inflammatory signaling in the CNS.…”
Section: Discussionsupporting
confidence: 76%
“…The combination of high serum cytokines and endothelial activation may lead to a cascade that could amplify endothelial activation and BBB permeability, allowing diffusion of high systemic concentrations of cytokines and trafficking of T cells into the CNS . The in vitro evidence of BBB disruption is supported by postmortem studies in patients who developed severe CRS and neurotoxicity that progressed to a fatal cerebral edema . In one case, a thrombotic microangiopathy with endothelial activation and vascular disruption was observed, along with perivascular CD8 + T cell infiltration .…”
Section: Neurotoxicitymentioning
confidence: 96%
“…In one case, a thrombotic microangiopathy with endothelial activation and vascular disruption was observed, along with perivascular CD8 + T cell infiltration . In autopsy cases, T cell infiltration has been reported as being absent, or localized to perivascular sites or the brain parenchyma; no uniform pattern has emerged . In a nonhuman primate model of CD20‐targeted CAR‐T cells, neurotoxicity was associated with both CAR and non‐CAR‐T cell accumulation in the CSF and brain along with increased concentrations of multiple proinflammatory cytokines in the CSF .…”
Section: Neurotoxicitymentioning
confidence: 98%
“…Necropsy from a nonhuman primate monkey model showed brain intraparenchymal infiltration of CAR‐T cells. CAR‐T cells were not seen on autopsy of a patient who died from cerebral edema on the JCAR015 study, despite seeing signs of blood‐brain barrier dysfunction . However, the patient received steroid treatment, and it is possible that there was preautopsy lysis of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…CAR-T cells were not seen on autopsy of a patient who died from cerebral edema on the JCAR015 study, despite seeing signs of blood-brain barrier dysfunction. 17,18 However, the patient received steroid treatment, and it is possible that there was preautopsy lysis of lymphocytes. The predictors contributing to the risk of developing neurotoxicity are not clear, but factors that have been associated are higher disease burden, higher CAR-T expansion, peak CAR-T counts, and the presence of extramedullary disease at the time of infusion.…”
Section: Discussionmentioning
confidence: 99%